ISRAT DALAM KITAB HALAIN KARYA AHMAD AL-SA - Hakim Mahfud (IAIN Kediri, 2019)
ISRAIILIYYATin HASHIYAH AL-SAWIY ‘ALA TAFSIR JALALAINAttitudeSyaikhal-Sawiy Against ActsIsraiIliyyat(Attitude in the Book ofHashiyah) is based on the many history of Isra iIliyya t contained in Hashiyah al-S awiy so that the number of readers who are not selective about stories that are not necessarily true. The author examines the attitude of Syaikh al-Sawiy on the story of Israiliyyat contained in hashiyah al-sawiy ‘ala tafsir jalalayn. With the aim of knowing whether or not the critical attitude of Syaikh al-Sawiy towards the story of IsraiIliyyat. The author uses the Research library method (literature). To obtain information from various sources the author uses the Documentation method then analyzes the data using a discourse analysis method developed by Tuen A.van Djijk namely macro structure, superstructure, and microstructure. The results of this study revealed that: The attitude of Syaikh al-Sawiyon the story of Israiliyyat in Hashiyahnot all the stories of Israiliyyathe commented. There are several stories that he included his sanad, but he immediately relies on the origin of history. There are also those who do not include the sanad at all. There are some narrations that he did not comment on and there is also a history that he commented on.Keyword: Israiliyyat, attitude of Shaihkal-Sawiy, and Hashiyah al-Sawiy